Cognitive stimulation therapy (CST) for dementia: a systematic review of qualitative research. (27th May 2021) - Gibbor, Luke; Yates, Lauren; Volkmer, Anna; Spector, Aimee
Abstract: Introduction: Cognitive Stimulation Therapy (CST) is a well-established intervention for people with dementia shown to improve cognition and quality of life. Past research includes development of a longer term 'maintenance CST' and an individual CST programme. Previous reviews of CST have focused on quantitative outcomes or excluded certain formats of CST. This review aimed to fill this gap by evaluating how the voices of facilitators, carers and people with dementia in qualitative studies of CST can contribute to our understanding of its implementation and how it is experienced. Methods: The current systematic review explored the experience and perspectives of people with dementia, facilitators and carers. Thematic Analysis was used to analyse this data, alongside guidance on synthesising qualitative findings. Results: A systematic literature search retrieved 10 relevant studies using qualitative methodology. Eighteen themes were generated, which were grouped into three categories: 'Acceptability and feasibility', 'Features of CST' and 'Key outcomes'. Conclusions: To our knowledge, this is the only review to explore solely qualitative studies of CST. Findings provided insight into the shared features, outcomes and factors affecting implementation, and suggested theories for discrepancies between quantitative and qualitative findings in the literature. Some of the common themes were also in keeping with past reviews.